Pelatihan dan Pengembangan Untuk Meningkatkan Keterampilan Karyawan Era Digital - Novi Anisa Safitri; Muhammad Fahmi Ilmiawan; Dini Islami; Muammar Khadavi; Muhammad Isa Ansori (International Forum of Researchers and Lecturers, 2024)
Training and development is an important aspect in almost all companies or organizations because it leads to increased performance in the required areas. Training is an important learning process in organizations that care about productivity. Each individual is encouraged and given training to continuously improve their skills and expertise throughout their career. Skilled and highly motivated people contribute greatly to work productivity. In improving an employee's performance, the most important supporting factor is the level of skills the employee possesses. Skills refer to a person's ability to carry out a task or job. Training and development provides opportunities for employees to acquire new skills or improve existing skills so that they are relevant to the needs of the ever-growing digital era. Training and development can improve employee skills in facing the challenges of the digital era. Training that focuses on information and communication technology (ICT), such as using the latest software or understanding data analytics, can help employees keep up with rapid technological developments in today's digital era.